Early literacy stimulation of preschool children using instructional media and prhophet guidance - Ruhaena, Lisnawati; Jauharoh, Su’ad; Chusniatun, Chusniatun (Jurnal Psikologi Islam, 2017)
Interaction of mothers and their preschool children could benefit as a stimulation of children’s letter recognition at home. This research is aimed to explore how mothers interact and used learning media in stimulating children’s early literacy skills. Data was collected by observation and interview. There were three dyad mother-children participated in this research, each of them using flash card, story book, and exercise book as learning media to introduce letters. The children were 2-5 years old and they lived in Surakarta. The result showes that during interaction, mothers gave scaffolding to their children and encouraged children to learn. While learning media supported the stimulating interaction and children early literacy skills. However children were still moody in responding to early literacy stimulation. How the findings are compared to Prophet Muhammad suggestion in children education were discussed. In conclusion, all of participants applied the interaction pattern from the Prophet Guidance and stimulated by their own in different ways. Keywords: mother- child interaction, the introduction of literacy, learning media.